THE EFFECT OF CONCEPT SENTENCE MODEL ON STUDENTS’ WRITING PERSUASIVE PARAGRAPH (A Study at The Tenth Grade Students of SMK Negeri 1 Sarudik 2017/2018 Academic Year) - astri yunita caniago (JURNAL LINER (Language Intelligence and Educational Research), 2019)
The purpose of this research is to find: 1)the application of concept sentence model. 2) the extent of the students’ Achiement in Writing persuasive paragraph before and after using Concept sentence model. 3) whether there is any significant effect of concept sentence model on students’ achievement in writing persuasive paragraph at the X grade of SMK Negeri 1 Sarudik. Method of the ruler was the experimental. The population of this research was all of the tenth grade students of SMK Negeri 1 Sarudik. It consist 109 students. Purposive sampling technique was uses to get a sample it consist 30 students. The technique for collecting data by observation sheet and giving test. The result mean score of the application of Concept Sentence Model was 3.8, it was “Very Good”.The result show score before using concept sentence model was 59.3 categorized “Fail”. While the mean score of the students’ achievement in writing persuasive paragraph after using concept sentence model was 68.46 categorized “Enough”. The result of ttest was 12.33 and ttable was 2.04 it means that there is a significant effect of using Concept Sentence Model on students’ achievement in writing persuasive paragraph at the tenth grade students of SMK Negeri 1 Sarudik 2017/2018 Academic Year)